Central Nervous System Strongyloidiasis and Cryptococcosis in an HIV-Infected Patient Starting Antiretroviral Therapy - Mónica Rodríguez; Paúl Flores; Víctor Ahumada; Lorena Vázquez-Vázquez; Claudia Alvarado-de la Barrera; Gustavo Reyes-Terán (Case Reports in Medicine)
We report a case of Strongyloides stercoralis hyperinfection syndrome with central nervous system involvement, in a patient with late human immunodeficiency virus (HIV) infection starting antiretroviral therapy, in whom Strongyloides stercoralis larvae and Cryptococcus neoformans were isolated antemortem from cerebrospinal fluid. Our patient was not from an endemic region for the parasite, so strongyloidiasis was not originally suspected. For this reason, we conclude that Strongyloides stercoralis infection should be suspected in HIV-infected patients starting antiretroviral therapy in order to avoid potential fatal outcomes.